2021
DOI: 10.3390/socsci10040127
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Mitigating Effect of Co-Parenting on Parental Burnout: The Gender Dimension Applied to COVID-19 Restrictions and Parental Burnout Levels

Abstract: Parenting is recognized as a complex and stressful activity, which in recent years has been linked to the potential development of parental burnout among mothers and fathers. With the spread of COVID-19 around the globe, not only have situations of health emergency and economic difficulty emerged, but also tremendous impacts on individual lives and family role divisions, which continue to be experienced today. As lockdown measures have affected unemployment rates, financial insecurity levels, social support, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Although previous studies have found coparenting support protected against parental burnout ( Mikolajczak & Roskam, 2018 ), findings on parenting during the COVID-19 pandemic were mixed. For example, in a study conducted by Bastiaansen et al (2021) the relationship between pandemic restrictions and parental burnout was not impacted by coparenting in general. However, coparenting did mitigate the impact of the restrictions on parental burnout among fathers.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Although previous studies have found coparenting support protected against parental burnout ( Mikolajczak & Roskam, 2018 ), findings on parenting during the COVID-19 pandemic were mixed. For example, in a study conducted by Bastiaansen et al (2021) the relationship between pandemic restrictions and parental burnout was not impacted by coparenting in general. However, coparenting did mitigate the impact of the restrictions on parental burnout among fathers.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is consistent with BR 2 and supports previous findings demonstrating coparenting support is a protective factor against parental burnout ( Mikolajczak & Roskam, 2018 ). Few studies have explored the effect of coparenting support on parental burnout ( Bastiaansen et al, 2021 ), and even less is known regarding the effect of coparenting support on parental burnout during COVID-19. Thus, the current finding is important in the context of the ongoing COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Managing the parent–child and family relationships during the pandemic is not only a family issue but also a social issue. There are numerous new perspectives for analyzing family social relations during the pandemic, which have included focusing on parenting stress in young parents ( Adams et al, 2021 ), parenting styles and parent–child relationships ( Chung et al, 2020 ), differences in parenting attitudes ( Forbes et al, 2021 ), parental psychological flexibility ( Gould et al, 2020 ), and the relationship between parenting and parental burnout ( Bastiaansen et al, 2021 ). For the underprivileged group of urban mothers ( Mazumdar et al, 2021 ), the COVID-19 pandemic has further detached their child-rearing practices from their daily life and derailed their socialization process.…”
Section: Introductionmentioning
confidence: 99%